Relationship between muscle morphological characteristics and pedaling power for elite track cyclists - Ikeda,Y.; Takashima, W.; Homma, T.; Takahashi, H.; Murata, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2013)
The purpose of this study was to clarify the relationship between the cross-sectional area (CSA) of the trunk and thigh muscles and power during maximum pedaling, and to investigate gender differences in trunk and thigh muscle sizes in cyclists. The subjects were 12 male and 9 female cyclists. Male cyclists completed 10 seconds of maximum pedaling using 3 different loads of 3, 7, and 11 kp, and female cyclists underwent the same test using loads of 2, 6, and 10 kp. The CSA of the trunk and thigh muscles was measured using magnetic resonance imaging. The relative values of the CSA were divided by the lean body mass (LBM)0.67, and the area of each muscle was calculated as a percentage of the total muscle cross-sectional area in the trunk and thigh. These relative values for the vastus medialis, sartorius, and psoas major were significantly greater in male than in female cyclists. The value of the maximal pedaling power (Pmax) relative to body mass (BM) ranged from 17.3 to 22.5 W/kg in male cyclists, and from 14.4 to 17.1 W/kg in female cyclists. The value of the mean power during 10 seconds of maximal pedaling (Pmean) divided by the LBM was significantly greater in male cyclists than in female cyclists at all loads. Pmean was shown to be closely correlated with the CSA of the trunk and thigh in male cyclists, whereas the relationship between Pmean and CSA in female cyclists was different from that in male cyclists. For male cyclists, significant positive correlations were observed between Pmean and the CSA of the thigh muscles, the psoas major, and the erector spinae at loads of 3 and 7 kp. In addition, the optimal pedaling rate at which Pmax was attained was significantly correlated with the CSA of the psoas major. These results indicate that hip flexion strength is an important factor for improving the sprint performance of highly trained male cyclists, while the extension strength of the knee and hip joints is clearly important for exerting a high Pmax.